Pengaruh Motivasi, Kompensasi dan Komitmen Organisasional Terhadap Kinerja Kryawan (Studi Pada PT. Boga Makmur Gracia Kendal) - Puspitasari, Putri; Yunianto, Askar (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to analyze the influence of motivation, compensation and organizational commitment on employee performance at PT. Boga Makmur Gracia Kendal. The type of data used is primary data sourced from questionnaires. The population in this study were employees of PT. Boga Makmur Gracia Kendal. The sampling technique used purposive sampling and obtained a sample of 110. In this research the test equipment used was validity testing using factor analysis, reliability testing using Cronbach Alpha and also hypothesis testing using multiple linear aggression. The results of this research state that motivation has a positive and significant effect on employee performance. Compensation has a positive and significant effect on employee performance. Organizational commitment has a positive and insignificant effect on employee performance.